COVID AND CHANGES IN BLOOD CLOTTING (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the relationship between COVID-19 infection and alterations in blood clotting mechanisms. Since the onset of the pandemic, clinical evidence has demonstrated that COVID-19 is not only a respiratory disease but also a systemic condition with significant hematological complications. Patients with severe forms of COVID-19 frequently exhibit abnormalities in coagulation, including increased risk of venous thromboembolism, disseminated intravascular coagulation (DIC), and microthrombi in vital organs. The article examines the underlying pathophysiological mechanisms, clinical manifestations, diagnostic challenges, and therapeutic strategies related to coagulation disorders in COVID-19. Particular attention is given to the role of endothelial dysfunction, hyperinflammatory response, and cytokine storm in promoting a hypercoagulable state.